ABOUT INDUSTRIAL METHODS FOR 3D PRINTING OF METALLIC MATERIALS - Cătălin IANCU; Yury GUTSALENKO (Fiabilitate şi Durabilitate)
In this paper is presented a presented a documentary research on the latest developments regarding the methods used in 3D printing of metallic materials, methods that exceed the already classic 3D printing of polymers or photo-polymerizable resin. The topic is important especially for industry where 3D printing technology can shift and use directly metallic materials for special purposes.